Modelling Seismic Risk in Greece Methodology, Applications, and Perspective - Kassaras, I.; D. Kazantzidou-Firtinidou; Kalantoni, D.; A. Ganas; Pomonis, A.; M. Gaspari; Giannaraki, G.; P. Kalantonis; C. Karakostas; Kaviris, G.; V. Kouskouna; Lekkas, E.; et al. (Safe Athens 2017, 2017)
During the last six years, our working group elaborated intense work on seismic risk assessment in several Greek cities, targeting site-specific models and allowing for tailor-made management actions in case of a crisis. In this paper we will present the main framework and the outcome of the applied methodologies on several case studies, indicating pros and cons, and highlighting future perspectives. Our approach includes: (a) Probabilistic and deterministic seismic hazard assessment based on comprehensive To this, new data concerning the location, geometry, and the seismic potential of faults, together with free-field ambient noise recordings have been collected through numerous field surveys; (b) Vulnerability assessment of elements at risk informed by newly created observed damage databases and in-situ observations; (c) Development of physical risk models including structural damage, and economic loss for several ground motion excitations scenarios. Future improvements that fall in with, and/or are beyond the current state-of-the-art, include: (a) and vulnerability assessment; (b) Socioeconomic impact analyses towards the mitigation of risk, enhancement of preparedness and resilience of the social and economic fabric, and (c) Applications for near real-time damage assessment by implementation of state-of-the-art opensource software (e.g. RASOR; OpenQuake